Nonlinear behaviour of different flexible size-dependent beams models based on the modified couple stress theory. Part 2. Chaotic dynamics of flexible beams; International Journal of Non-Linear Mechanics; Vol. 93 - Krysko A. V. Anton Vadimovich; Awrejcewicz J. Jan; Zhigalov M. V. Maksim; Pavlov S. P.; Krysko V. A. Vadim (2017, 2017)
Title screen